2020
DOI: 10.1186/s40104-020-00515-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics-data-assisted genomic feature markers preselection improves the accuracy of genomic prediction

Abstract: Background Presently, multi-omics data (e.g., genomics, transcriptomics, proteomics, and metabolomics) are available to improve genomic predictors. Omics data not only offers new data layers for genomic prediction but also provides a bridge between organismal phenotypes and genome variation that cannot be readily captured at the genome sequence level. Therefore, using multi-omics data to select feature markers is a feasible strategy to improve the accuracy of genomic prediction. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…In species where reference genome or high-quality genome assembly is available, the incorporation of SNPs with biological functions ( i.e. , multi-omics) improved the prediction accuracy, for instance, about 5–19% for fertility traits in dairy cattle ( Abdollahi-Arpanahi et al 2017 ; Nani et al 2019 ), or 27.4–60.7% for traits in inbred lines of Drosophila ( Ye et al 2020 ). Unfortunately, a good genome assembly is currently not available for striped catfish ( Kim et al 2018 ), this area thus deserves future studies to enable the efficient utilization of genomic information in the genetic selection program for this economically important species in the aquaculture sector.…”
Section: Discussionmentioning
confidence: 99%
“…In species where reference genome or high-quality genome assembly is available, the incorporation of SNPs with biological functions ( i.e. , multi-omics) improved the prediction accuracy, for instance, about 5–19% for fertility traits in dairy cattle ( Abdollahi-Arpanahi et al 2017 ; Nani et al 2019 ), or 27.4–60.7% for traits in inbred lines of Drosophila ( Ye et al 2020 ). Unfortunately, a good genome assembly is currently not available for striped catfish ( Kim et al 2018 ), this area thus deserves future studies to enable the efficient utilization of genomic information in the genetic selection program for this economically important species in the aquaculture sector.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavior of eQTLs in this study was observed only for a single phenotype with low resolution genotyping data. Also, Ye et al (2020) were successful in improving the performance of phenotype prediction in Drosophila using genotypes of eQTLs regulating genes that are important for the phenotype. They proceeded with successive selection steps involving a transcriptome wide association study (TWAS) with an eQTLs analysis for the TWAS significant genes, while optimizing the detection thresholds of these two analyses.…”
Section: Integration Success Is Driven By the Loss In Importance Of Covariation Sources Between Genomics And Transcriptomicsmentioning
confidence: 99%
“…Such integration can happen for a given omic type over different datasets or populations, each one summarized by its own model, with a final global model feeding on the top features contributed by each of the initial models. Another variant of the same model-based integration proceeds through a multistage approach, combining sequentially different omics for a given population (Ye et al, 2020). One of the simplest integration approaches, however, remains data concatenation (Azodi et al, 2020), by which multiple omics are placed side by side into a single large input matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several multi-omics prediction studies have been reported in cereal and animal species (Guo et al 2016 ; Riedelsheimer et al 2012 ; Schrag et al 2018 ; Wang et al 2019 ; Westhues et al 2017 ; Xu et al 2017 ; Xu et al 2021 ; Ye et al 2020 ; Zhao et al 2015 ). These studies have shed light on the merits of multi-omics prediction over traditional genomic prediction and discussed useful statistical methods for integrating omics data.…”
Section: Introductionmentioning
confidence: 99%